2007
DOI: 10.1063/1.2434940
|View full text |Cite
|
Sign up to set email alerts
|

Third-order nonlinear optical properties of bismuth-borate glasses measured by conventional and thermally managed eclipse Z scan

Abstract: Third-order nonlinearity one order of magnitude larger than silica is measured in bismuth-borate glasses presenting a fast response ͑Ͻ200 fs͒. The results for the sign and magnitude of the nonlinearity were obtained using a combination of the eclipse Z scan with thermal nonlinearity managed Z scan, whereas the Kerr shutter technique was employed to obtain the electronic time response of the nonlinearity, all performed with 76 MHz repetition rate 150 fs pulses at 800 nm. Conventional Z scans in the picosecond r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…The third-order nonlinearity of BZH2 had been measured at 1064 nm by Gomes et al and found to be 60 × 10 − 22 m 2 /V 2 that is 30 times higher than the χ (3) in silica glass [22]. The χ (3) of BZH7 and BZH4 is estimated from the refractive index using the Miller's rule [10] and found to be 33× 10 − 22 m 2 /V 2 and 16.5 × 10 − 22 m 2 /V 2 respectively.…”
Section: Glass Samplesmentioning
confidence: 97%
See 1 more Smart Citation
“…The third-order nonlinearity of BZH2 had been measured at 1064 nm by Gomes et al and found to be 60 × 10 − 22 m 2 /V 2 that is 30 times higher than the χ (3) in silica glass [22]. The χ (3) of BZH7 and BZH4 is estimated from the refractive index using the Miller's rule [10] and found to be 33× 10 − 22 m 2 /V 2 and 16.5 × 10 − 22 m 2 /V 2 respectively.…”
Section: Glass Samplesmentioning
confidence: 97%
“…[17] for the poling of BZH2, BZH7, BZH4 and BZH6 bulk glasses. L: sample thickness, t d : thickness of the depletion region, V: poling voltage, χ (3) of BZH2 was measured in [22]. χ (3) of BZH7, BZH4 and BZH6 estimated according to Miller's rule (see Section 3.1).…”
Section: Theoretical Constraintsmentioning
confidence: 99%
“…19 The new technique was introduced recently for studies of liquids, solids, and biomaterials. 7,17 TM-EZ scan technique presents the sensitivity of eclipse Z scan and gives the simultaneous measurements of the nonthermal and thermal nonlinearities of the material under study. The use of lasers with high repetition rate allows measurements with large sensitivity and better signal-to-noise figure.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In particular, compositions of HMO glasses containing lead and/or bismuth are strong candidates and have been studied in the past few years. [6][7][8][9][10] Recent measurements with bismuth oxide based glasses from the femtosecond to the nanosecond regime 6,7 demonstrated that the presence of heavy-metal atoms is very important to enhance the nonlinearity. Previous studies using pulses of 35 and 100 fs at wavelengths in the range of 600-1250 nm also revealed increasing of the HMO glasses nonlinearity with the increase of heavy-metal content.…”
mentioning
confidence: 99%
“…As we known, addition of heavy metal oxides can enhance third-order nonlinearity. As a heavy metal ion, W 6+ with empty d orbital can form groups with O 2-that have large polarizability in glass network, which leads to the increase of nonlinear refraction γ. Consequently, the sample glass BBW6 with the highest WO 3 content gets a maximal value of γ, namely 1.173×10 -14 cm 2 /W, which is larger than that of Bi 2 O 3 -B 2 O 3 -ZnO [21] . …”
Section: Third-order Optical Nonlinearitymentioning
confidence: 96%